2017
DOI: 10.1038/s41598-017-11949-9
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of PD-L1 expression and its prognostic impact after concurrent chemoradiation therapy in non-small cell lung cancer patients

Abstract: Concurrent chemoradiation therapy (CCRT) is the treatment of choice for locally advanced non-small cell lung cancer (LA-NSCLC). Several clinical trials that combine programmed cell death 1 (PD-1) axis inhibitors with radiotherapy are in development for patients with LA-NSCLC. However, the effect of CCRT on programmed cell death ligand-1 (PD-L1) expression on tumor cells is unknown. In this study, we analysed paired NSCLC specimens that had been obtained pre- and post-CCRT. PD-L1 expression on tumor cells was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
75
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 45 publications
(36 reference statements)
7
75
1
Order By: Relevance
“…Non‐small cell lung cancer is known to upregulate PD‐L1 expression, and high PD‐L1 expression is an independent predictor of poor prognosis . In the present study, we found that 32 NSCLC samples (56.1%) stained negative for PD‐L1, and 25 NSCLC samples (43.9%) stained positive for PD‐L1 (Figure A,B).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Non‐small cell lung cancer is known to upregulate PD‐L1 expression, and high PD‐L1 expression is an independent predictor of poor prognosis . In the present study, we found that 32 NSCLC samples (56.1%) stained negative for PD‐L1, and 25 NSCLC samples (43.9%) stained positive for PD‐L1 (Figure A,B).…”
Section: Resultssupporting
confidence: 57%
“…We found that high expression of PD‐L1 in tumor cells is significantly correlated with a high number of circulating Tfh cells in NSCLC patients. NSCLC patients with PD‐L1‐negative tumor cells had longer disease‐free survival, as reported in other studies . Gu‐Trantien et al 25 found that when Tfh cell infiltration in breast cancer patients was greater, the prognosis of patients was better.…”
Section: Discussionsupporting
confidence: 62%
“…Discordance in PD‐L1 expression occurred more frequently in patients who had received neoadjuvant therapy, and was associated predominantly with positive PD‐L1 assay in TURB and negative assay at matched cystectomy. The effect of neoadjuvant therapy on PD‐L1 expression might be due to immune suppressive effects of chemotherapy, which has also been observed in breast and non‐small‐cell lung cancer …”
Section: Discussionmentioning
confidence: 93%
“…The effect of neoadjuvant therapy on PD-L1 expression might be due to immune suppressive effects of chemotherapy, which has also been observed in breast and non-small-cell lung cancer. 9,10 Two recent studies investigated the concordance of different PD-L1 assays in urothelial cancer tissue microarrays, and found PD-L1 expression in 12-29% of samples. 11,12 Tretiakova et al found concordant PD-L1 assay outcome in matched primary urothelial carcinoma and lymph node metastasis in 90%.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 expression in tumor cells is altered by host immunity and during, for example, chemotherapy, tyrosine kinase inhibitor therapy, and immunotherapy. [14][15][16] Thus, our findings suggest that during the clinical course of lung cancer, the PD-L1 expression, including that in cytology/fluid material, is influenced by histology, genetic factors, medical treatment history, and the basal PD-L1 expression level of the tumor.…”
Section: Discussionmentioning
confidence: 83%